Food consumption and nutrient intake in Italian school children: results of the ZOOM8 study. (12th March 2013) - Martone, Deborah; Roccaldo, Romana; Censi, Laura; Toti, Elisabetta; Catasta, Giovina; D'Addesa, Dina; Carletti, Claudia; ,
Abstract: The food consumption and food habits of Italian third-class-primary-school children were assessed and their energy and nutrient intakes were compared with requirements. The study involved 1740 subjects (900 males and 840 females) aged 8–9 years, from the north, centre and south of Italy. Body weight and height were measured. Parents filled in a semi-quantitative Food Frequency Questionnaire for their child. The results showed that the diet of Italian children is unbalanced in terms of macronutrients and deficient in fiber. The average daily intakes of fruit (234 g/d), vegetables (134 g/d) and legumes (17 g/d), were lower than the nationally recommended ones. The percentages of energy intake from fats (41%) and from carbohydrates (45%) were higher and lower respectively than recommended. Low intakes of fiber (13.5 g/d) were reported. A national nutrition policy in Italy should focus on nutrition education programs in schools and for parents.